Oligopeptide Targeting Sortase A as Potential Anti-infective Therapy for Staphylococcus aureus - Wang, Jianfeng; Li, Hongen; Pan, Juan; Dong, Jing; Zhou, Xuan; Niu, Xiaodi; Deng, Xuming (Frontiers in Microbiology, 2018)
Sortase A (SrtA)-catalyzed anchorage of surface proteins in most Gram-positive bacteria is indispensable for their virulence, suggesting that this transpeptidase is a promising target for antivirulence therapy. Here, an oligopeptide, LPRDA, was identified as an effective inhibitor of SrtA via virtual screening based on the LPXTG substrate sequence, and it was found to inhibit SrtA activity in vitro and in vivo (IC50=10.61 μM) by competitively occupying the active site of SrtA. Further, the oligopeptide treatment had no anti-S. aureus activity, but it provided protection against S. aureus-induced mastitis in a mouse model. These findings indicate that the oligopeptide could be used as an effective anti-infective agent for the treatment of infection caused by S. aureus or other Gram-positive bacteria via the targeting of SrtA.